Abundance and Stability as Common Properties of Allergens - Foo, Alexander C. Y.; Mueller, Geoffrey A. (Frontiers in Allergy, 2021)
There have been many attempts to identify common biophysical properties which differentiate allergens from their non-immunogenic counterparts. This review will focus on recent studies which examine two such factors: abundance and stability. Anecdotal accounts have speculated that the elevated abundance of potential allergens would increase the likelihood of human exposure and thus the probability of sensitization. Similarly, the stability of potential allergens dictates its ability to remain a viable immunogen during the transfer from the source to humans. This stability could also increase the resilience of potential allergens to both gastric and endosomal degradation, further skewing the immune system toward allergy. Statistical analyses confirm both abundance and stability as common properties of allergens, while epidemiological surveys show a correlation between exposure levels (abundance) and allergic disease. Additional studies show that changes in protein stability can predictably alter gastric/endosomal processing and immunogenicity, providing a mechanistic link between stability and allergenicity. However, notable exceptions exist to both hypotheses which highlight the multifaceted nature of immunological sensitization, and further inform our understanding of some of these other factors and their contribution to allergic disease.